2015
DOI: 10.1007/s10654-015-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid weather changes are associated with increased ischemic stroke risk: a case-crossover study

Abstract: Observational studies focusing on absolute meteorological values suggest an association between meteorological parameters and stroke risk but these results are inconsistent and conflicting. Since changes in weather can provoke atrial fibrillation, we examined the association between rapid weather changes and stroke risk in 1694 patients with determinable onset of stroke symptoms in a case-crossover study in central Germany. Days one to three before stroke onset were classified as hazard periods and day seven a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 27 publications
3
38
2
Order By: Relevance
“…Sex and age differences are apparent in stroke incidence, severity and prognosis [ 44 , 45 ]. With regards to temperature, the effects of sex on the association between ambient temperature and IS risk are in line with previous reports [ 25 , 38 , 46 ], but there is absence of evidence of gender differences for ICH and SAH. A recent meta-analysis reported that the association between ambient temperature and stroke occurrence was irrelevant for those who were 18 to 64 years old, but it is stronger among the elderly (≥65 years).…”
Section: Discussionsupporting
confidence: 89%
“…Sex and age differences are apparent in stroke incidence, severity and prognosis [ 44 , 45 ]. With regards to temperature, the effects of sex on the association between ambient temperature and IS risk are in line with previous reports [ 25 , 38 , 46 ], but there is absence of evidence of gender differences for ICH and SAH. A recent meta-analysis reported that the association between ambient temperature and stroke occurrence was irrelevant for those who were 18 to 64 years old, but it is stronger among the elderly (≥65 years).…”
Section: Discussionsupporting
confidence: 89%
“…In hospital-based studies with analysis based on subtypes, cardioembolic stroke was generally most common in winter, and other subtypes of stroke were common in warmer seasons. 15,35,36 However, one should be careful about discussing seasonal variation of stroke onset based on single-center studies, because there might be some differences in the prehospital comes (mRS), and a relatively high follow-up rate at 1 year, exceeding four-fifths. When the present patients were divided into cardioembolic and noncardioembolic stroke groups, the former showed a winter-excess frequency, and the latter showed an insignificant peak in summer.…”
Section: Analysis Of Patients With Noncardioembolic Strokementioning
confidence: 99%
“…Second, the season might be a rougher explanatory variable than other meteorological conditions such as temperature, atmospheric pressure, relative humidity, and newer social environments such as air pollution. 16,[18][19][20]36,42 Third, it was difficult to clarify the definite results of noncardioembolic stroke patients divided by 3 further subtypes because of the small patient numbers. Fourth, recent therapeutic strategies such as endovascular thrombectomy and direct oral anticoagulants were adopted rapidly during the 5-year study period.…”
Section: Study Limitationsmentioning
confidence: 99%
“…This approach is an established and efficient variation of the case-control study design and examines the association between a brief and transient exposure and the risk for the onset of an acute and rare event [17]. For example, we and others have successfully applied the case-crossover study design to examine the relationships between atmospheric conditions and ischemic stroke [18], myocardial infarction [19], or epileptic seizures [20]. In contrast to the case-control approach, data in this casecrossover study are analyzed by intraindividual comparison of meteorological conditions shortly before the onset of BP with meteorological conditions that were present in the same patient's recent past.…”
Section: Discussionmentioning
confidence: 99%